2011
DOI: 10.1017/s1751731110001771
|View full text |Cite
|
Sign up to set email alerts
|

The effect of equol injection in ovo on posthatch growth, meat quality and antioxidation in broilers

Abstract: In order to investigate the long-term effects of equol (Eq) on growth and meat quality in broilers, 0 mg (control, Con), 20 mg (low dose, L) and 100 mg (high dose, H) Eq, respectively, were injected into fertile eggs (146 eggs per group) on 7 days of embryos. After hatch, chickens were fed under the same conditions and slaughtered at 49 days of age for sample collection and analysis. The results showed that body weight and composition were marginally affected by Eq administration ( P . 0.05). Compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
1
9
0
2
Order By: Relevance
“…In this context, in order to obtain favorable broiler meat quality, the modulation of the embryo nutritional supply in the incubation stage is a promising solution. Indeed, evidence has shown that administration of equol, L-ascorbic acid, or synbiotics in the incubation phase may effectively improve broiler meat quality [3,[7][8][9]. Since the risk for protein catabolism in late embryos exists [10], it is interesting to probe the efficacy of IOF of amino acids on meat quality of market size broilers.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, in order to obtain favorable broiler meat quality, the modulation of the embryo nutritional supply in the incubation stage is a promising solution. Indeed, evidence has shown that administration of equol, L-ascorbic acid, or synbiotics in the incubation phase may effectively improve broiler meat quality [3,[7][8][9]. Since the risk for protein catabolism in late embryos exists [10], it is interesting to probe the efficacy of IOF of amino acids on meat quality of market size broilers.…”
Section: Introductionmentioning
confidence: 99%
“…Representative photomicrographs of comet assay in broiler muscle cells (×100 and equol on human health and diseases, in association with their antioxidant capacities. Our previous studies showed that in ovo injection of equol, as well as dietary supplementation with daidzein significantly improved the muscle water-holding capacity of broilers through improved antioxidant status (Wei et al 2010). The waterholding capacity of the muscle is related to the integrity of the muscle cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that in ovo injection of equol significantly improved muscle water-holding capacity, which is related to improved antioxidant status in broilers (Wei et al 2010). A study in normotensive rats also demonstrated substantial vasodilating and antioxidant activities of equol in cerebral arteries, with similar activity to daidzein (Jackman et al 2007).…”
Section: Introductionmentioning
confidence: 90%
“…In our experiment, dietary supplements with 1% lactulose significantly increased the T-SOD and CuZn-SOD activity in the liver of barrows treated with daidzein (Table 5). The antioxidant ability of pure equol in humans, cells, and rats is widely established [40], [41]. However, to our knowledge, no information is available on the effects of a hydrogen-producing prebiotic that increases equol production and improves antioxidants status in vivo .…”
Section: Discussionmentioning
confidence: 99%